Factors That Effect The Nosokomial Phlebitis Infections in Hospital Bhayangkara TK II. H.S. Samsoeri Mertojoso Surabaya - Sepvi Fitriyanti (Universitas Airlangga, 2015)
Nosokomial phlebitis infections, the cause of it about 60% of patients treated receiving invasive procedures, and the incidence of phlebitis nearly 4%. This research aims to learn the factors that effect the nosokomial phlebitis infections, in recognition of these factors is expected to be the input for Samsoeri Mertojoso Hospital in Surabaya. To reduce the incidence of nosokomial phlebitis infections in order to improve the better quality of care in hospital. This researce use cross-sectional method, this research take sample consisted of 68 respondents, and 22 respondents exposed with pblebitis, while 46 respondents are not exposed with phlebitis. In this research, the factors observed were internal factors, such aa: age, gender and disease. And the external factors, such as the size of the needle, the type of fluid infusion, the location of the stabbing infusion, intravena treatment (infusion), the duration of intravena (infusion) installation and infusion installation techniques. From the analysis of the table obtained proportion of the risk of phlebitis incidence in patients based upon age (OR = 59.5), gender (OR = 2.487), disease (OR = 6.249), needle size (OR = 0.019), the type of fluid administered (OR = 18,943), the location of the stabbing infusion (OR = 2.4), infusion treatment (OR = 6.818), duration of infusion installation (OR = 14.286) and infusion installation techniques (OR = 4.048). The conclusion of this research is that the type of fluid variables have a greater effect on the incidence of phlebitis at Bhayangkara hospital in Surabaya. dan based on these results, it is suggested attention of the hospital officers, especially standard procedures of infusion installation againts factors that influence the phlebitis. and the need for surveillance and nosokomial teams of infection control in hospital. Keywords: nosokomial infections, phlebitis infection